Design and Experimental Tests of a Four-Way Valve with the Determination of Flow Characteristics for Building Central Heating Installations Using Solid Modeling - Niekurzak, Mariusz; Mikulik, Jerzy (Energies (Basel), 2024)
The article presents the design of a four-way valve, implemented in SolidWorks software (SOLIDWORKS® i 3DEXPERIENCE® Works Simulation) and used for central heating installations in buildings. The project was carried out in order to examine the innovative design of the medium mixing mechanism and to conduct strength and FMEA analysis. The innovative solutions proposed by the authors in this work will allow valves of this type to meet stringent environmental standards. These standards are currently being introduced for this type of structural element of machine parts as part of the energy transformation of buildings. Potential failures occurring in individual elements of the four-way valve were also tested using Failure mode and effects analysis. In addition, strength tests were performed in SolidWorks software using static analysis, and optimization tests were performed on the refrigerant in terms of its impact on the environment. The characteristics of the tested materials in the valve design show that the best materials are brass and stainless steel. Brass has a Poisson’s ratio of 0.33, a tensile strength of 478.4 MPa and a yield strength of 239.7 MPa. In turn, stainless steel is characterized by the following parameters: Poisson’s ratio of 0.27, tensile strength of 685 MPa and yield strength of 292 MPa. The designed valve reduces energy consumption by 30% through a properly designed medium flow with the appropriate selection of materials. Moreover, the design reduces the thickness of the contaminant layer by 0.17 mm, with a capacity factor of −2.50% and an evaporator Δp of 3.10% (53 kPa). The performed research provides knowledge on the subject selection of appropriate material, a description of the potential failures of the structural elements of the designed four-way valve and methods of counteracting these failures. The article presents the optimization role of the tested component in the context of sustainable development.